Harina de hojas de plantas medicinales como aditivo fitobiótico en dietas para codorniz de engorde - Suarez Ordoñez, Jazmín Alejandra (2021)
Food represents the highest percentage of investment in poultry production, so producers are looking for ways to improve their production parameters by adding different additives, among which growth-promoting antibiotics are used the most. The objective of this study was to evaluate the productive behavior of quail (Coturnix coturnix japonica) using mixed flour from the leaves of medicinal plants as a phytobiotic additive in the diet; which were included at supplementation levels of 0 (T1); 0.50 (T2); 1.00 (T3); 1.50 (T4)% of mixed powder of leaves of medicinal plants of Morinda citrifolia L. (noni), Psidium guajava L. (guava), Annona muricata L. (soursop) and Jatropha curcas L. (pine nut of tempate), in a ratio of 40: 20: 20: 20, respectively. A completely randomized design (DCA) with four treatments and five repetitions was applied. To determine the statistical differences, the Tukey test (P≤0.05) was used. 160 quail with 8 days of age were used, the investigation lasted 6 weeks. Feed intake (g), weight gain (g), feed conversion, carcass yield (%), morphometric measurements, mortality and economic analysis were evaluated. The productive parameters were not affected when supplying this flour, however, statistical differences were found in terms of weight gain, registering a value of 146.18 g for the control treatment. Regarding feed conversion, the lowest value was obtained by treatment T1 (6.72) and the highest value T2 (9.00). On the other hand, the quail's gastrointestinal tract was not affected by the addition of this phytobiotic in terms of its size. In the economic profitability, Treatment 2 obtained 17.77% with a cost benefit ratio of $ 1.18, referring to the fact that we will earn 17 cents. for every dollar invested. Key words: quail, phytobiotic, productive performance, profitability.